2010
DOI: 10.1074/jbc.m110.135509
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue-specific Inhibition of Hypoxia-inducible Factor 1α Induces Obesity and Glucose Intolerance by Impeding Energy Expenditure in Mice*

Abstract: Hypoxia in adipose tissue has been postulated as a possible contributor to obesity-related chronic inflammation, insulin resistance, and metabolic dysfunction. HIF1␣ (hypoxia-inducible factor 1␣), a master signal mediator of hypoxia response, is elevated in obese adipose tissue. However, the role of HIF1␣ in obesity-related pathologies remains to be determined. Here we show that transgenic mice with adipose tissue-selective expression of a dominant negative version of HIF1␣ developed more severe obesity and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
74
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 41 publications
6
74
1
Order By: Relevance
“…Several studies have reported that adipose tissue expansion in response to HFD is accompanied by hypoxia, which could potentially elicit pro-angiogenic signaling and a subsequent expansion of the capillary network (35). However, hypoxia signaling in adipose tissue appears to result in fibrosis, rather than in angiogenesis (15,38). An alternative possibility is that expansion of the adipose tissue capillary network is triggered by factors that accompany excessive energy consumption.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies have reported that adipose tissue expansion in response to HFD is accompanied by hypoxia, which could potentially elicit pro-angiogenic signaling and a subsequent expansion of the capillary network (35). However, hypoxia signaling in adipose tissue appears to result in fibrosis, rather than in angiogenesis (15,38). An alternative possibility is that expansion of the adipose tissue capillary network is triggered by factors that accompany excessive energy consumption.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, our observation is supported by several lines of evidence from genetically modified mice. 30,38,39 Overexpression of a dominant-negative form of HIF-1α in adipocytes accelerated HFD-induced glucose intolerance and insulin resistance and induced more severe obesity. 38 Another study showed that factor inhibiting HIF-1α-deficient mice that have elevated HIF activity are also resistant to HFD-induced body weight gain and glucose intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…30,38,39 Overexpression of a dominant-negative form of HIF-1α in adipocytes accelerated HFD-induced glucose intolerance and insulin resistance and induced more severe obesity. 38 Another study showed that factor inhibiting HIF-1α-deficient mice that have elevated HIF activity are also resistant to HFD-induced body weight gain and glucose intolerance. 39 This evidence consistently suggests that HIF signaling is positively linked to resistance to obesity and associated metabolic abnormalities.…”
Section: Role Of Phd2 In Adipocytes 2085mentioning
confidence: 99%
“…In this regard, there is evidence to suggest that HIF1a protein accumulates in adipocytes of obese humans and mouse models of obesity (Ye 2009). While mouse models wherein HIF1a has been either overexpressed (Halberg et al 2009), deleted in WAT (Jiang et al 2011), or expressed as a dominant-negative form (Zhang et al 2010) have been generated, they have not been suitable to interrogate a specific requirement of HIF1a function for maintaining the obese state (as opposed to the development of the obese state) and its associated pathologies. Hence, it remains unclear whether and how HIF1a function contributes to the maintenance of adiposity and its associated pathologies in the context of a pre-existing obese, diabetic, and cardiomyopathic state.…”
mentioning
confidence: 99%